A Needs Assessment of Edutainment Module with Ethnoscience Approach Oriented to the Love of the Country - Ardianti, S. D.; Wanabuliandari, S.; Saptono, S.; Alimah, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
In this globalization era, young generations are having problems regarding the love of the country character. The purposes of this research were (1) analyzing students’ need on an entertaining module; (2) analyzing students’ need on learning with ethnoscience approach; and (3) analyzing students’ need on building the love of the country character. This research is qualitative research involving 5th-grade students of IT Umar bin Khattab Elementary school as the subject. A purposive sampling technique used, where the research instruments included questionnaires, interviews, and documentation studies. The data analysis involved several steps, namely, data reduction, categorization, validity checkings, interpretation, and inferences. The result of this research showed that the government and particular publisher distributed the learning material used by students. The teacher had never given any innovation by using culture based-learning for improving the love of country character to the students. Besides, the questionnaire showed that the students expected an entertaining learning material with stories, picture, and fun activity. However, based on the result, the edutainment module with ethnoscience approach was needed for improving students’ love of the country character.